Using clinician and patient input to assess utility, accuracy, efficiency, and therapeutic implementation of a new data-driven digital therapeutic for personalized clinical eating disorder treatment: Awaken digital guide. - Ralph-Nearman, Christina; Rae, Jesse; Levinson, Cheri A. (Psychotherapy Research, 2025)
Objective: Eating disorders (EDs) take a life every 52 minutes and treatments are ineffective for ∼50% of individuals. Though EDs are heterogeneous illnesses, current evidence-based treatments take a "one-size-fits-all" approach. Network-Informed Personalized Treatment is a new promising treatment for EDs, but clinician-patient-friendly software tools are needed to integrate this guidance system into routine treatment. Adoption is key for impact, necessitating the inclusion of clinicians in the software development. The current pilot assessed a new data-driven clinician-guidance therapeutic. Method: A two-part pilot was analyzed for quantitative (0-not at all to 10-extremely) and qualitative input on user perception through quantitative and open-ended prompted questions evaluating using personalizing ED treatment with the Awaken Digital Guide therapeutic. Results: Results demonstrated that clinicians in a focus group (N = 9) and clinician/patient dyads within implementation (N = 10) endorsed improved efficiency, effectiveness, self-awareness, and accuracy using Awaken Digital Guide compared to current treatment as suggested by quantitative and qualitative results. Both clinicians and patients rated the tool positively (6.8-9.6/5.8-8.6, respectively) with an average rating of good and excellent. Conclusion: Findings suggest that ED-specialized clinicians desire data-driven guidance on personalizing ED treatment. Users perceive Awaken Digital Guide therapeutic with potential to increase collaboration, motivation, efficiency, and effectiveness of ED personalized treatment.